“Kuliah Agama” notification based on location via mobile application / Mohamad Akmal Shukri Mahmud - Mahmud, Mohamad Akmal Shukri (2015)
Knowledge is very important to our life. Gaining knowledge is a virtue for all Muslims regardless of age and gender. It is a compulsory for all Muslims. Attending themselves to a “Kuliah Agama” is a platform for the Muslims to gain more knowledge about Islam. With this, they can fulfill their responsibility and career as a Muslims without doubt since their questions about Islam would be answered. However, there are still some obstructions to get an accurate and efficient timetable for the “Kuliah Agama”. Thus, this mobile application will provide the information of “Kuliah Agama” which is information about date, time, title, ustaz’s name and location that will be updated by mosque’s committee. Notification is a part that provided in this application, it will notify the community about schedule of “Kuliah Agama” at specific date and time. Therefore, it will avoid the community to miss the schedule of “Kuliah Agama”. The location of mosque and location of community also plays an important role in determines the availability the schedule of “Kuliah Agama”. The community will only get the nearest mosque with current location to view the schedule. It used the Location Based Services (LBS) which is GPS technique to trace the precise location of community and mosque. The project developed based on the improvised of agile methodology. This methodology will be the guideline to make sure this project succeed. After this application is launched, the objectives of this project have achieved because the community in Jasin and Merlimau will get information of “Kuliah Agama” at their nearest location without missed any notification about schedule of “Kuliah Agama”. The scope of this project is only focusing on a few mosques in Merlimau and Jasin. In future work, it will be available entire in Melaka.